A climate rationale for research and development on photovoltaics manufacture. (1st March 2017) - Ravikumar, Dwarakanath; Wender, Ben; Seager, Thomas P.; Fraser, Matthew P.; Tao, Meng
Highlights: Current research underestimates climate impact of PV manufacturing GHGs. Radiative forcing quantifies time-sensitive climate impact of GHGs over PV lifecycle. GHG intensity of electricity used to manufacture PV is a significant climate hotspot. Climate benefit of low-carbon PV manufacture equivalent to 4% module efficiency gain. Manufacturing oriented R&D should complement R&D on module efficiency improvements. Abstract: Photovoltaic (PV) power generation is critical to many climate policy goals, as PV electricity results in little or no greenhouse gas (GHG) emissions during use, utilities and governments view PV installations as a way to accelerate progress towards emissions reduction targets. However, typical analyses of the GHG implications of the PV lifecycle ignore inter-temporal effects, in which the initial GHGs emitted in PV manufacturing phase must be offset by avoided fossil-fuel combustion emissions during use. Thus, the overall climate benefits of PV are a function of both GHG efficiency of PV manufacture, and electricity generation efficiency of deployed modules during use. Improvements to PV manufacture result in immediate climate benefits, in contrast with improvements in module efficiency which may offset greater GHG emissions, albeit over decades of useful life. This study presents a novel framework using the cumulative radiative forcing (CRF) metric to demonstrate the significant climate benefit of improving PV manufacturing processes predominantly located in GHG-intensive geographies and determines the equivalent increase in module efficiency that provide the same climate benefit. The findings show low-carbon PV manufacturing increases the life-cycle climate benefit by 20% and is equivalent to increasing the module efficiency from a baseline value of 17% to 21.7% and 16% to 18.7% for mono-Si and multi-Si modules, respectively. With commercial module efficiency having increased annually by only 0.25% over the last 12 years, the implication is that improving PV manufacturing may be more effective than module efficiency improvements for increasing the climate benefit of terawatt scale PV installations.